A Sociolinguistics Analysis of Cross-Gender Interaction in the Movie “10 Things I hate About You” Based on Deborah Tannen’s Theory - Lusiana Rachmawati (SEMINAR NASIONAL SOSIAL, SAINS, PENDIDIKAN, HUMANIORA (SENASSDRA), 2023)
This research analyzed the existence of conflict in the interaction between men and women characters in the movie “10 Things I Hate About you.” The analysis was based on Deborah Tannen’s theory of men and women language. In Deborah Tannen’s book entitled “You Just Don’t Understand” published in 1990, discussing theory about language and gender. The aims of this study is to describe Deborah Tannen's theory applied by the characters in the movie “10 Things I hate about you”. To complete this research, researcher used qualitative research design. The data was taken from conversation between men and women character in the movie. To collect the data researcher used documentation method. The researcher finds that there are six conflicts exist in interaction occur between men and women characters in the movie. There are status vs. support, independence vs. intimacy, advice vs. understanding, information vs. feelings, orders vs. proposals, and conflict vs. compromise.